(untitled) (The Journal of Plant Protection Sciences, 2022)
Biocontrol agents like beneficial insects, para sitoids, predators, pathogens etc. are essential elements of biological control of insect pests (6). Success of using this parasitoid in biocon trol programme usually depends not only on the availability of their insect hosts but some times on a complex system of other factors such as additional food sources, alternate hosts and shelter (5,6). Earlier research work ers (3,1,2) indicated that the most favourable combinations of natural enemies would be those that tend to parasitize or prey on differ ent optimum/suitable stages of the host.